Indirect lightning performance of 10-kV overhead distribution lines - Yu, Jianli; Gu, Shanmao; Liu, Jianjun; Liu, He (Frontiers in Energy Research, 2024)
This study comprehensively analyzed the characteristics of lightning-induced voltage for the improvement of lightning protection of overhead lines. The lightning-induced voltage in 10-kV overhead distribution lines was calculated and analyzed using the Agrawal coupling model and second-order finite difference-time domain (FDTD) method. The influence of lightning position on lightning-induced voltage was analyzed using the concept of indirect lightning withstanding levels. The results indicated that the lightning-induced voltage amplitude at the point nearest to the lightning position is not necessarily the highest. Moreover, the waveform and amplitude of the induced voltage at the symmetrical positions on both sides of the point are not symmetrically distributed. Lightning position has notable influence on the pulse polarity reversal of lightning-induced voltage. The pulse amplitude decreases with the decreasing distance from the polarity-reversal position. When the installation density of surge arresters is relatively low, strong negative-polarity oscillations occur because of the influence of the surge arresters. Finally, to achieve the limiting effect on lightninginduced voltage in 10-kV lines, the installation density of surge arresters should not be less than 1 group per 200-300 m.